How to Eat Like a Canadian: Centennial Cookbooks and Visions of Culinary Identity - Wilmshurst, Sara (Cuizine)

(untitled) (McGill University Library, 2013)
This article examines selected cookbooks that were published for the Canadian centennial year: the Chatelaine Centennial Collection of Home-Tested Recipes, Food – à la canadienne by the federal Department of Agriculture’s consumer section, and Pierre and Janet Berton’s Centennial Food Guide. These cookbooks and the recipes they contain tell us a great deal about the performance of citizenship through cookery. This article asks: who are the food makers? Who are the eaters? Whose recipes are included, or excluded and, accordingly, validated or marginalized? The result is a highly selective vision of Canadian identity.